An Expeditious Green Cascade Synthesis of 3‐Arylideneaminoquinazolin‐4(1H)‐one Derivatives via 'Solvent Drop Grinding' and Their Antioxidant and DNA Protective Studies. Issue 8 (17th June 2016) - Kuntikana, Sahana; Bhat, Chinmay; Kongot, Manasa; Bhat, Subrahmanya I; Kumar, Amit
Abstract: An unprecedented, green protocol for the combinatorial synthesis of 3‐arylideneaminoquinazolin‐4(1 H )‐ones is explored by a 'solvent assisted grinding' reaction of o ‐aminobenzhydrazide and aldehydes/ketones. The present methodology found special utility by overcoming the problems associated with commercial 'ball milling' and 'solvent‐ free grindstone' techniques. The operational simplicity, product selectivity, short reaction time, high yield, and wide functional group tolerance are the promising advantages of the current protocol. The antioxidant activity of the selected products was studied using 2‐diphenyl‐1‐picrylhydrazyl (DPPH) radical scavenging technique and compounds which displayed considerable antioxidant activity were screened for their protective ability against Deoxyribonucleic acid (DNA) damage. Abstract : Unusual 'Solvent drop' grinding method employed for the synthesis of various 3 arylideneaminoquinazolin‐4(1 H )‐one compounds which exhibit excellent radical scavenging activity